Circulating tumour cell detection: a direct comparison between the CellSearch System, the AdnaTest and CK-19/mammaglobin RT–PCR in patients with metastatic breast cancer - Van der Auwera, I (Nature Publishing Group, 2010)
BACKGROUND: The detection, enumeration and isolation of circulating tumour cells (CTCs) have considerable potential to influence the clinical management of patients with breast cancer. There is, however, substantial variability in the rates of positive samples using existing detection techniques. The lack of standardisation of technology hampers the implementation of CTC measurement in clinical routine practice. METHODS: This study was designed to directly compare three techniques for detecting CTCs in blood samples taken from 76 patients with metastatic breast cancer (MBC) and from 20 healthy controls: the CellSearch CTC System, the AdnaTest Breast Cancer Select/Detect and a previously developed real-time qRT-PCR assay for the detection of CK-19 and mammaglobin transcripts. RESULTS: As a result, 36% of patients with MBC were positive by the CellSearch System, 22% by the AdnaTest, 26% using RT–PCR for CK-19 and 54% using RT–PCR for mammaglobin. Samples were significantly more likely to be positive for at least one mRNA marker using RT–PCR than using the CellSearch System (P=0.001) or the AdnaTest (P<0.001). CONCLUSION: We observed a substantial variation in the detection rates of CTCs in blood from breast cancer patients using three different techniques. A higher rate of positive samples was observed using a combined qRT-PCR approach for CK-19 and mammaglobin, which suggests that this is currently the most sensitive technique for detecting CTCs.